STRATEGI PENGEMBANGAN USAHA ALAT MUSIK DI TOKO SULTAN MUSIK KELURAHAN SIRANINDI KOTA PALU - Ristamala Ristamala; Fitri Almirah Maulidya; Harifa Harifa; Yulvianti Hamidu; Moh Yusuf; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Strategy is an important step in determining the long-term plan of an organization. The development of musical instrument business in the Sultan Music shop is crucial considering the increasing demand for musical instruments and increasingly tight competition, especially from online sales. This study aims to determine the business development strategy at the Sultan Music Shop. With a focus on overcoming the challenges or obstacles faced and identifying strategic steps that can increase competitiveness. This study was analyzed descriptively Qualitatively with a case study approach at the Sultan Music shop. Primary data was collected through interviews with shop owners and employees while secondary data was obtained from documentation and related literature. This study shows that the Sultan Music Shop faces significant challenges in the musical instrument industry, including intense competition and the need to increase brand recognition. In this context, an effective business development strategy is essential to improve product and service quality. Sellers need to have a deep understanding of the products offered in order to explain their advantages and facilities to consumers.